2017
DOI: 10.1161/atvbaha.117.309007
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-III Levels and Incident Coronary Artery Disease Risk

Abstract: Objective Apolipoprotein C-III (apoC-III) is a key regulator of triglyceride (TG) metabolism. Elevated TG rich lipoproteins and apoC-III levels are causally linked to coronary artery disease (CAD) risk. The mechanism(s) through which apoC-III increases CAD risk remains largely unknown. The aim was to confirm the association between apoC-III plasma levels and CAD risk and to explore which lipoprotein subfractions contribute to this relationship between apoC-III and CAD risk. Approach and Results Plasma apoC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 27 publications
4
32
1
Order By: Relevance
“…In this study, food intake per 100 g of body weight was lower in animals consuming added sugars compared to the control group, but only the effect of sucrose was statistically significant. Similar results were obtained by Tsanzi et al (2008) and Light et al (2009) who found that food intake in animals on a sucrose diet was lower compared to those on HFCS-55 diet. The glycemic index (GI) is regarded as one of the most significant factors affecting food consumption.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, food intake per 100 g of body weight was lower in animals consuming added sugars compared to the control group, but only the effect of sucrose was statistically significant. Similar results were obtained by Tsanzi et al (2008) and Light et al (2009) who found that food intake in animals on a sucrose diet was lower compared to those on HFCS-55 diet. The glycemic index (GI) is regarded as one of the most significant factors affecting food consumption.…”
Section: Discussionsupporting
confidence: 88%
“…It has been found that the amount of added sugars had a significant effect on body weight gains in the tested animals, regardless of sugar type. Similar results were obtained by Light et al (2009) and Tsanzi et al (2008). In contrast, Bocarsly et al (2010) observed higher weight gains in animals on an HFCS diet than animals on a sucrose diet.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These apos were found to be strong predictors of CVD [ 17 ]. The association of apoCIII with incident CVD was further corroborated by Van Capelleveen et al [ 18 ] in a nested case–control study of the EPIC-Norfolk cohort. As residual cardiovascular risk remains high [ 8 ] even after successful treatment of traditional risk factors, a case–control study with long-term follow-up of patients with STEMI was executed to evaluate the value of extensive serum apo profiling for (1) prediction of STEMI and for (2) prediction of recurrent major adverse cardiac events (MACE) in patients with STEMI.…”
Section: Introductionmentioning
confidence: 54%
“…The VLDL-associated apos apoCII, apoE and—to a large extent—apoCIII have recently been identified as potentially important new risk factors [ 17 , 18 ]. These apos are abundant on TG-rich lipoproteins, strongly modulate their metabolism [ 39 ], and might play an important role in the development of atherosclerosis and subsequent CVD.…”
Section: Discussionmentioning
confidence: 99%